Effect of oxygen on the lungs after blast injury and burns. Issue 10 (October 1981) - Hasleton, P S; Penna, P; Torry, J
Abstract : In March 1979 there was an explosion in a coalmine in Lancashire. As a result three men were found dead down the mine and a further seven men, all with extensive burns, died between the third and thirteenth day after the explosion. The lungs were studied in all the cases. Pulmonary infection was the commonest cause of death. Despite high levels of oxygen being given to these seven men, only one case showed a focal intra-alveolar fibrosis. In this case the inspired oxygen requirement came down before death. The toxicity of oxygen in the short term management of patients with severe trauma is questioned.